2008
DOI: 10.1038/nm1725
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the neurocristopathy Treacher Collins syndrome through inhibition of p53 function

Abstract: Treacher Collins syndrome (TCS) is a congenital disorder of craniofacial development arising from mutations in TCOF1, which encodes the nucleolar phosphoprotein Treacle. Haploinsufficiency of Tcof1 perturbs mature ribosome biogenesis, resulting in stabilization of p53 and the cyclin G1-mediated cell-cycle arrest that underpins the specificity of neuroepithelial apoptosis and neural crest cell hypoplasia characteristic of TCS. Here we show that inhibition of p53 prevents cyclin G1-driven apoptotic elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
495
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(521 citation statements)
references
References 31 publications
19
495
1
6
Order By: Relevance
“…They also complement a recent analysis of pancreas-specific deletion of murine Sbds (Tourlakis et al, 2012), and implicate defective proliferation of ptf1a-expressing pancreatic progenitor cells as a basis for the observed pancreatic phenotype. The zebrafish Sbds knockdown phenotype was not rescued by loss of p53, suggesting that, in contrast to Treacher Collins syndrome and 5q-syndrome (Jones et al, 2008;Barlow et al, 2010), SDS is a largely p53-independent ribosomopathy. Furthermore, by unbiased screening of genes exhibiting altered expression following Sbds knockdown, we have identified a previously unappreciated requirement for additional genes related to ribosome assembly in early pancreas development.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…They also complement a recent analysis of pancreas-specific deletion of murine Sbds (Tourlakis et al, 2012), and implicate defective proliferation of ptf1a-expressing pancreatic progenitor cells as a basis for the observed pancreatic phenotype. The zebrafish Sbds knockdown phenotype was not rescued by loss of p53, suggesting that, in contrast to Treacher Collins syndrome and 5q-syndrome (Jones et al, 2008;Barlow et al, 2010), SDS is a largely p53-independent ribosomopathy. Furthermore, by unbiased screening of genes exhibiting altered expression following Sbds knockdown, we have identified a previously unappreciated requirement for additional genes related to ribosome assembly in early pancreas development.…”
Section: Discussionmentioning
confidence: 94%
“…When normal ribosome biogenesis is disrupted, a resulting p53 response is commonly accepted to play a role in the associated disease phenotypes (Lohrum et al, 2003;Dai and Lu, 2004;Jin et al, 2004;Danilova et al, 2008;Jones et al, 2008;Barlow et al, 2010;Duan et al, 2011;Sasaki et al, 2011). To determine whether SDS disease phenotypes are similarly p53 dependent, we evaluated the influence of p53 inactivation on the organogenesis defects induced by Sbds ATG MO injection, using both MO-mediated p53 knockdown and available p53 mutant alleles.…”
Section: Loss Of P53 Does Not Rescue the Sbds Organogenesis Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Interestingly, a study by Jones et al showed that chemical and genetic inhibition of p53 activity in these mice can prevent the craniofacial abnormalities. 72 This is of special note, and the link between p53 and ribosomopathies is discussed in greater detail later in this review.…”
Section: Treacher Collins Syndromementioning
confidence: 96%
“…However, mice with a point mutation in rps19 do have a hematopoietic defect that is rescued by p53 knockdown[11]. p53 inactivation also rescues craniofacial abnormalities in mouse models of Treacher Collins Syndrome, where mutations affect ribosome biogenesis[12]. In a mouse model of conditional rps6 knockdown, p53 is activated[13].…”
Section: Introductionmentioning
confidence: 99%